Atmospheric Sb in the Arctic during the past 16,000 years: responses to climate change and human impacts - Krachler, Michael; Zheng, Jiancheng; Fisher, David; Shotyk, William (Global biogeochemical cycles, 2008)
Applying strict clean room procedures and sector field inductively coupled plasma mass spectrometry (ICP-MS) methods, concentrations of Sb and Sc were determined in 57 sections of a 170.6-m-long ice core drilled on Devon Island, Arctic Canada, in 1999, providing a record of atmospheric Sb extending back 15,800 years. Natural background concentrations of Sb and Sc established during the period between 1300 years BP and 10,590 years BP averaged 0.08 ± 0.03 pg/g (N = 18) and 0.44 ± 0.20 pg/g (N = 17), respectively. Scandium, a conservative reference element, was used as a surrogate for mineral dust inputs. The Sb/Sc ratio of 0.13 ± 0.07 in these ancient ice samples is comparable to the corresponding ratio of 0.09 ± 0.03 in peat samples from Switzerland from circa 6000 to 9000 years BP, indicating that this natural background ratio might have a much broader validity. The natural background flux of Sb (0.7 ± 0.5 ng/m2/a) in the Arctic was approximately 500 times lower than that established in central Europe using peat cores. For comparison with background values, modern Sb fluxes calculated using 45 samples from a 5-m snow pit dug on Devon Island in 2004, reflecting 10 years of snow accumulation, yielded an average deposition rate of 340 ± 270 ng/m2/a (range: 20-1240 ng/m2/a) with pronounced accumulation of Sb during winter periods when air masses reaching the Arctic predominantly come from Eurasia. These data reveal that approximately 99.8% of the Sb deposited in the Arctic today originates from anthropogenic activities. Modern Sb enrichment factors averaged 25 (range: 8-121). The ice core provides evidence of Sb contamination dating from Phoenician/Greek, Roman, and medieval lead mining and smelting in Europe. Moreover, the ice core data indicate that anthropogenic sources of Sb have continuously dominated the atmospheric inputs to the Arctic for at least 700 years.
Gesehen am 28.09.2020